2012
DOI: 10.1007/s10875-012-9766-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased T-Cell Activation and Th1 Cytokine Concentrations Prior to the Diagnosis of B-Cell Lymphoma in HIV Infected Patients

Abstract: A higher level of T-cell activation, Th1 cytokine serum concentration and markers of EBV replication, preceded B-cell lymphoma diagnosis. This may suggest that viral antigen stimulation is associated with the genesis of lymphoma in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
1
4
1
Order By: Relevance
“…In contrast to recent studies by others who concluded that AIDS-NHL risk was associated with either a TH1 (15) or TH2 cytokine pattern (14) preceding NHL diagnosis, there was no strong association seen between most of the TH1 or TH2 cytokines tested and AIDS-NHL risk.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to recent studies by others who concluded that AIDS-NHL risk was associated with either a TH1 (15) or TH2 cytokine pattern (14) preceding NHL diagnosis, there was no strong association seen between most of the TH1 or TH2 cytokines tested and AIDS-NHL risk.…”
Section: Discussioncontrasting
confidence: 99%
“…While initially considered to be a TH2 cytokine, IL-10 is produced by regulatory T cells (Treg) (40), and by monocyte/macrophages, and is a potent B cell-stimulatory factor (41). IP-10, which was strongly associated with risk for AIDS-NHL in this study, as well as in prior work by others (15), is produced by activated macrophages (39). Additionally we found that neopterin, which is an established biomarker for macrophage activation (27,28), is strongly associated with risk for AIDS-NHL.…”
Section: Discussionsupporting
confidence: 89%
“…Of particular interest for A-NHL is IP-10, a leukocyte chemoattractant implicated in the development and progression of B-cell lymphoma. In two recent studies, elevated levels of IP-10 in the sera of HIV-positive individuals were associated with the development of B-cell lymphoma within 0–5 years 22 , [44]. Elevated pretreatment serum levels of IP-10 were also associated with increased likelihood of disease relapse and diminished survival in HIV-uninfected patients with diffuse large B-cell lymphoma [45].…”
Section: Discussionmentioning
confidence: 95%
“…31,49,59 Other researchers have also reported increased cytokines 60,61 or B cell activation markers (FLC) 62 pre-AIDS-NHL diagnosis. Most recently, Vendrame et al looked at TH1, TH2, and TH17/T follicular helper cells (TFH) cytokines, using multiplexed (Luminex platform) assays, during the one to five years preceding AIDS-NHL diagnosis in 180 AIDS-NHL cases in the MACS.…”
Section: Role Of Immune Activation In Aids-nhl: Epidemiological mentioning
confidence: 98%